CSR disclosure and financial performance revisited: A cross-country analysis. Issue 4 (November 2018) - Beck, Cornelia; Frost, Geoffrey; Jones, Stewart
The relationship between corporate social responsibility (CSR) and corporate financial performance (CFP) has been the subject of intensive research. However, limitations with this literature include the use of localised samples, poorly specified control variables and self-constructed CSR disclosure measures that may not represent a firm's actual CSR performance. Answering the call for 'better' CSR research in this field, as well as extending research to a cross-country analysis, this study examines the relationship between corporate CSR engagement (measured by diversity in voluntary disclosure practices) and financial performance across three reporting jurisdictions: Australia, Hong Kong and the United Kingdom. We use the Global Reporting Initiative (GRI) framework to rate companies on their CSR engagement and control for actual CSR performance using the Vigeo-Eiris CSR sustainability ratings as the proxy measure. Based on a sample of 116 large public companies, we find evidence that CSR engagement can be indicative of actual CSR performance. We also find evidence of a significant relationship between CSR engagement and financial performance, even after controlling for the CSR performance proxy, firm size, industry-level fixed effects, financial risk and type of assurer. The results appear to be robust across national reporting jurisdictions and alternative CSR metrics constructed from the CSR engagement measure. JEL classification:M41, M14